2014
DOI: 10.1016/j.jpain.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Survival Patterns in Squamous Cell Carcinoma of the Head and Neck: Pain as an Independent Prognostic Factor for Survival

Abstract: Survival outcomes in patients with squamous cell carcinoma of the head and neck (HNSCC) vary by extent of disease, behavioral, and socioeconomic factors. We assessed the extent to which pre-treatment pain influences survival in 2340 newly diagnosed patients with HNSCC, adjusting for disease stage, symptoms, pain medications, comorbidities, smoking, alcohol consumption, age, sex, and race/ethnicity. Patients rated their pain at presentation to the cancer center (0= ‘no pain’ and 10= ‘pain as bad as you can imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
79
2
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 35 publications
7
79
2
2
Order By: Relevance
“…In an analysis of 2,340 HNSCC patients, Reyes-Gibby et al found that the presence of severe pretreatment pain in oral and pharyngeal cancers predicted significantly worse 5-year overall survival, even after accounting for disease stage and other relevant clinical factors. 16 Thompson et al showed that pain severity immediately following treatment and 2 years after treatment were significant factors associated with overall survival in patients with HNSCC. 17 In our cohort, opioid use at 3, 6, and 12 months after treatment correlated with worse overall survival (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In an analysis of 2,340 HNSCC patients, Reyes-Gibby et al found that the presence of severe pretreatment pain in oral and pharyngeal cancers predicted significantly worse 5-year overall survival, even after accounting for disease stage and other relevant clinical factors. 16 Thompson et al showed that pain severity immediately following treatment and 2 years after treatment were significant factors associated with overall survival in patients with HNSCC. 17 In our cohort, opioid use at 3, 6, and 12 months after treatment correlated with worse overall survival (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that HNC patients with lymph node metastases were more likely to report severe pretreatment pain compared to patients without lymph node involvement, and that this was significantly correlated with measures of overall quality of life and increased symptom burden. 4 Pre-treatment pain has been associated with poorer overall survival in patients with HNSCC 18 thus suggesting the need for prompt pain treatment and management.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance for both incidence (5,8,9) and prognosis of OPC (10) are smoking, alcohol intake and HPV16 infection (via sexual contact, including that of oral sex). Smoking and, to a lesser extent, heavy drinking at the time of diagnosis are both associated with increased incidence and poor prognosis (10)(11)(12). Interestingly, HPV16 infection, while being a risk factor for OPC incidence, has been associated with better prognosis (13)(14)(15), with a population-based study conducted in Boston from December 1999 to December 2003 demonstrating that HPV16 infected cases showed improved overall survival compared to those without an infection (HR: 0.1; 95% CI: 0.02-0.4; N: 448) (16).…”
Section: Introductionmentioning
confidence: 99%